Situation Analysis of the Drug Registration in Vietnam from 2009 To 2019 - Thi Hai Yen, Nguyen; Ngan, Thai Hue (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 2, 2021)
Vietnam is classified into the group of emerging pharmaceutical countries (Pharmerging) according to the classification of IMS Health since 2008. In order to achieve the potential, it is necessary to have a clear understanding of the status of drugs registered for circulation in Viet Nam. However, research on this issue has not been popular, lacked updating, and has not shown continuous change over a long period of time. Therefore, the study is conducted with the desire to provide an overview of the status of drug registration in Vietnam in the period 2009-2019. Classify "Drugs" according to the Law on Pharmacy No. 105/2016/QH13. Pharmaceutical and biological drugs are classified into 27 groups according to ATC codes based on Circular 30/2018/TT-BYT and Vaccine. 19 groups of dosage forms, classified according to the Vietnam Pharmacopoeia V. In the period 2009-2019, Vietnam has 45,801 registered drug registration numbers. In which, domestic drugs with 28,388 numbers (62%). India and South Korea are the 2 countries with the most number of registrations, accounting for 33.9% and 17.3% respectively. Chemico-pharmaceutical finished products registered with 42,245 numbers (92.2%). The group of drugs for treating parasites and anti-infections is the most registered with 27.1%. Oral and parenteral administration, infusion are the two main forms of administration, of which tablets are the most registered dosage form, accounting for 46.4%. Paracetamol is the most registered active ingredient with a total of 2262 registration numbers. Drugs produced domestically have partly met the needs of the people to use drugs, but there is still an imbalance between the pharmacological groups and registered active ingredients. Domestic pharmaceutical enterprises need to increase investment in and research active ingredients and drug groups with few registered numbers.   Keywords Drug registration number, active pharmaceutical ingredient, drug registration, period of 2009-2019, Vietnam . References